Association between Hypoadiponectinemia and Low Serum Concentrations of Calcium and Vitamin D in Women with Polycystic Ovary Syndrome. (16th January 2012) - Mazloomi Mazloomi, Sahar Sahar; Sharifi Sharifi, Faranak Faranak; Hajihosseini Hajihosseini, Reza Reza; Kalantari Kalantari, Sadroddin Sadroddin; Mazloomzadeh Mazloomzadeh, Saideh Saideh
Abstract : Objective . To investigate the possible association of calcium and vitamin D deficiency with hypoadiponectinemia in women with PCOS. Subjects and Methods . In this case-control study, 103 PCOS cases and 103 controls included. The concentrations of calcium, 25-OH-vitamin D (25OHD), adiponectin, insulin, glucose, total cholesterol, HDL-cholesterol, triglyceride (TG), and androgens were measured in fasting blood samples. Results . Adiponectin (8.4 ± 2.7 ng/mL versus 13.6 ± 5 ng/mL in control group, P : 0.00 ), calcium (2 ± 0.1 mmol/L versus 2.55 ± 0.17 mmol/L in controls, P : 0.00 ), and 25-OH-Vit D (30 ± 2.99 nmol/L versus 43.7 ± 5.2 nmol/L in control group, P : 0.00 ) levels were decreased in women with PCOS. Subjects with PCOS had higher concentrations of TG (1.4 ± 0.7 7 mmol/L versus 1.18 ± 0.75 mmol/L in control group, P : 0.019 ) and dehydroepiandrosterone sulfate (DHEA-S) (10.7 ± 11 mmol/L versus 9.7 ± 10.4, P : 0.02 in control group). There were significant correlations between adiponectin concentrations with calcium (r : 0.78, P : 0.00 ) and 25OHD levels (r : 0.82, P : 0.00 ). The association of hypoadiponectinemia and PCOS was not significant considering 25OHD as a confounding factor. Conclusion . The present findings indicate that the association of hypoadiponectinemia with PCOS is dependent on vitamin D. A possible beneficiary effect of vitamin D on the metabolic parameters in PCOS may be suggested.